Biosand Filter as a Household Water Treatment Technology in Ghana and its Ecobusiness Potential: An Assessment Using a Lifecycle Approach - Hogarh, Jonathan N.; Sowunmi, Fatai A.; Oluwafemi, Agbola P.; Antwi-Agyei, Philip; Nukpezah, Daniel; Atewamba, Calvin T. (Journal of Environmental Accounting and Management, 2026)
Biosand filter basically applies a system of sand, gravels and biologically active microorganisms to remove unwanted substances from drinking water. Field trials of the biosand filter for domestic water treatment in rural communities have shown remarkable health gains from its application. As such, there are calls to scale up its application in developing countries. This study investigated factors that may influence the acceptability of the biosand filter at the household level in rural communities in Ghana. The study further applied lifecycle environmental and cost assessments to analyse the eco-efficiency potential of the biosand filter and examined prospects of leveraging this potential for green business development. The key demographic and socio-economic indicators of biosand filter acceptability related to gender, age, education and wealth. Females showed greater interest in the biosand filter, while discrete increase in age, relative advancement in education and economic status of respondents may each increase the prospects of purchasing biosand filter. Compared to local sachet water production, which was considered as a quasialternative to the biosand filter, it was established that the latter has superior eco-efficiency, provided quite comparable profitability and potentially viable for eco-business development. The information yielded by this study is useful for scaling up considerations of the biosand filter technology in Ghana and other West African countries.